2001
DOI: 10.1159/000046566
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Abnormalities in Newly Diagnosed Adult Acute Myeloid Leukemia

Abstract: Retinal abnormalities (RA) are very frequently observed in adult patients with acute myeloid leukemia (AML), but the clinical significance of these findings has not been fully investigated. We examined the fundus oculi in a cohort of 122 adult patients with AML at presentation and analyzed some clinical and biological features to assess whether there was any association with RA. For this purpose, we subdivided the patients into two groups according to the presence or absence of RA (groups 1 and 2, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
1
1
Order By: Relevance
“…Retinopathy is an important clinical manifestation that determines poor prognosis in patients in the remission period. The complete remission rate and survival rate of young patients who do not have retinopathy are significantly higher than those of older patients with retinopathy (15). CML in the patient in the current study was detected at an early stage, and no cotton wool spots were observed in the fundus.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Retinopathy is an important clinical manifestation that determines poor prognosis in patients in the remission period. The complete remission rate and survival rate of young patients who do not have retinopathy are significantly higher than those of older patients with retinopathy (15). CML in the patient in the current study was detected at an early stage, and no cotton wool spots were observed in the fundus.…”
Section: Discussioncontrasting
confidence: 52%
“…In addition, the binocular retina had a large number of bleeding spots, and all bleeding spots had a white center. Specchia et al (15) reported that patients with leukemia who had retinopathy exhibited an increased level of blood lactate dehydrogenase, with an average of 812 IU/l, whilst patients who did not have retinopathy displayed a mean blood lactate dehydrogenase level of 607 IU/l. The blood lactate dehydrogenase level of the current patient was increased to 860 IU/l (normal range, 100-300 IU/l), which was consistent with the literature (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…loidní leukémie se vyskytuje častěji v dospělém věku, nárůst incidence pozorujeme u pacientů nad 65 let [12,18,19].…”
unclassified
“…Retinal abnormalities such as retinal haemorrhages and cotton‐wool spots are frequently observed in adult patients with acute myeloid leukaemia (Specchia et al 2001). Retinal neovascularization has been described in patients with chronic myelocytic and acute lymphocytic leukaemia (Wiznia et al 1994).…”
mentioning
confidence: 99%